Assessment method for potential educational technology competency standard based on TPCK in Malaysian Higher Education Institutions / Yau’Mee Hayati Hj Mohamed Yusof, Hamidah Jantan and Nur Muslimah Kamilah Abdullah - Mohamed Yusof, Yau’Mee Hayati; Jantan, Hamidah; Abdullah, Nur Muslimah Kamilah (Penerbit UiTM, 2018)
Technology in education is purposely designed to help both educators and students in knowledge transfer and knowledge gain simultaneously. In many aspects, technology in education is supposed to prove that education can be delivered effectively and efficiently. However, there are cases in which technology in education can be frustrating and annoying for both parties. Government and university management have invested a lot of money to ensure that educators and students can really benefit from the technology. In spite of huge investment on educational technology tools (hardware and software) over the past decades in various education initiatives, the potential of technology usage at university level has not reached the desired level among educators and students. What is the missing link for the realisation of the expected return-of-investment? Recent researches (C Akarawang, 2015; Bibi, 2017; Hersh, 2014) indicate that the problem is due to the gap between technical ICT skills and the knowledge of good pedagogical practice among educators. The outcome of this study proposes an Educational Technology standard to be applied in university setting using TPCK (Technological Pedagogical Content Knowledge) as the basic framework. However, this paper will only discuss a part of our standard development highlighting the assessment method that was used during the implementation of ETC standard in our institutions. Overall, the descriptive result using pre and post means scores as assessment method towards proposed standard shows that the educators’ acceptance score in our institutions are mostly good. However the element within the standard least accepted are TCK (Technology Content Knowledge) and TPK (Technology Pedagogical Knowledge). The assessment and finding in this study nevertheless are suggested to be used as a guidance for ETC Standard implementation in university setting in order to stress the importance of considering technological possibilities in light of developmentally appropriate practices and specific learning goals in ICT/ET training provided for educators in HEI in Malaysia.